Strategi Komunikasi Customer Journey UMKM Dalam Menghadapi Tantangan Dan Peluang Situasi The Messy Middle - Ikhma Zurani; Dedi Kusuma Habibie; Tengku Firli Musfar (Cakrawala - Jurnal Humaniora, 2023)
The study aims to identify the role and impact of the "middle messy" phase in the consumer journey towards brand marketing strategies. The ever-changing business era and the dynamics of consumer behavior require brands to adapt to complex environments. This research identifies the importance of the exploration and evaluation phases in the consumer journey, where consumers tend to be open to looking for new alternatives. The main objective of this research is to uncover how brands can take advantage of the opportunities that exist during this phase. The research method used involved in-depth interviews with clients who had just gone through the "dirty middle" phase. The data collected is then analyzed to find patterns of customer behavior, trends, and preferences during this phase. Research results show that smart and flexible brands can more effectively respond to market dynamics. They can leverage brand presence, apply relevant behavioral principles, and optimize consumer travel measures to maximize opportunities during the "middle messy" phase. The results of this study show that the "middle messy" phase is actually an opportunity for unestablished brands to attract consumer attention and preferences. It is important for brands to understand consumer behaviour during this phase, offer a different user experience, and provide relevant information. Brands can cope with challenges in uncertain situations and compete successfully by taking proactive and adaptive action. This research provides in-depth insight into how brands can respond to market dynamics and interact with consumers in an ever-changing era.